Wave‐based SHM of sandwich structures using cross‐sectional waves. Issue 2 (5th September 2017) - Droz, Christophe; Bareille, Olivier; Lainé, Jean‐Pierre; Ichchou, Mohamed N.
Summary: The identification of structural damage in composite waveguides is a critical issue in aerospace and transportation industries. Frequently, these structures involve periodic patterns or dissipative components that considerably reduce the range, robustness, and available bandwidth of ultrasonic structural health monitoring techniques. On the other hand, wave‐based methods provide more accurate information on a defect's type, size, and location than modal analysis techniques. This paper focuses on a low‐frequency wave‐based method for structural integrity assessment of complex waveguides. The wave finite element method is employed to compute the dispersion curves of non‐standard cross‐sectional waves exhibiting increased strain energy. The spectral results are used to analyse the diffusion of guided elastic waves through representative localized defects in a laminated sandwich panel. To validate the diffusion model, reflection and transmission coefficients are determined for several wave pulses on typical defects using time‐domain virtual experiments and cross‐sectional energy acquisition. Results demonstrate that using cross‐sectional waves provides a sensitivity to damage up to 2.8× higher than flexural waves in the low‐frequency range. These results are explained by the presence of local resonances within the cross section, producing wavelengths in the transverse direction of propagation. These waves may prove suitable for cost‐effective structural health monitoring applications because they can travel long distances through heterogeneous and periodic structures.